2021
DOI: 10.1016/j.bjid.2021.101609
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related hospital cost-outcome analysis: The impact of clinical and demographic factors

Abstract: Introduction Although patients’ clinical conditions have been shown to be associated with coronavirus disease (COVID-19) severity and outcome, their impact on hospital costs are not known. This economic evaluation of COVID-19 admissions aimed to assess direct and fixed hospital costs and describe their particularities in different clinical and demographic conditions and outcomes in the largest public hospital in Latin America, located in São Paulo, Brazil, where a whole institute was exclusively d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
5
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 22 publications
1
49
5
8
Order By: Relevance
“…The 75 th round of National Sample Survey (NSS) carried out in the year 2017 reports the average medical expenditure incurred during Hospitalisation was more than seven fold in a private hospital than in a government hospital (MOSPI, 2019). The analysis from the present study adds to a group of studies that have established that comorbid conditions are significantly associated with increasing medical costs for hospitalisations for COVID-19 (Carrera-Hueso et al, 2021;Chua et al, 2021;Miethke-Morais et al, 2021). Even though the existing body of evidence from low and middle income countries emphasizes on the role of health insurance in protecting households from catastrophic health costs,the present study did not identify such an association in the regression model (Huffman et al, 2011).…”
Section: (Which Was Not Certified By Peer Review) Preprintcontrasting
confidence: 68%
“…The 75 th round of National Sample Survey (NSS) carried out in the year 2017 reports the average medical expenditure incurred during Hospitalisation was more than seven fold in a private hospital than in a government hospital (MOSPI, 2019). The analysis from the present study adds to a group of studies that have established that comorbid conditions are significantly associated with increasing medical costs for hospitalisations for COVID-19 (Carrera-Hueso et al, 2021;Chua et al, 2021;Miethke-Morais et al, 2021). Even though the existing body of evidence from low and middle income countries emphasizes on the role of health insurance in protecting households from catastrophic health costs,the present study did not identify such an association in the regression model (Huffman et al, 2011).…”
Section: (Which Was Not Certified By Peer Review) Preprintcontrasting
confidence: 68%
“…36 The analysis from the present study adds to a group of studies that have established that comorbid conditions are significantly associated with increasing medical costs for hospitalizations for COVID-19. 23,24,37 Even though the existing body of evidence from low and middle income countries emphasizes the role of health insurance in protecting households from catastrophic health costs, the present study did not identify such an association in the regression model. 38 Recent research has demonstrated that coverage under the public health insurance programs for those below poverty line had no significant influence on decreasing OOP expenditure payments.…”
contrasting
confidence: 86%
“…Ohsfeldt et al in the US found that by increasing in the patient age, hospitalization cost decreased that is in line to the present finding [ 15 ]. Another study in the Brazil showed that hospitalization costs decreased by increasing in age, too [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of a systematic review showed that being a man was related to the severe COVID-19 [ 13 ], in our study, gender did not change the median cost in both hospitalization periods. Other studies in the US and the Brazil showed that men had a higher cost compared to women [ 15 , 16 ]. However, they did not divide patients based on the length of stay.…”
Section: Discussionmentioning
confidence: 99%